Formal [3+2] Cycloaddition of Ketenes and Oxaziridines Catalyzed by Chiral Lewis Bases: Enantioselective Synthesis of Oxazolin‐4‐ones - Shao, Pan‐Lin; Chen, Xiang‐Yu; Ye, Song (Angewandte Chemie (International ed.), 2010)
Choose the right cat.: A highly enantioselective synthesis of oxazolin‐4‐ones by the formal [3+2] cycloaddition of ketenes and a racemic oxaziridines has been developed (see scheme; cat.=N‐heterocyclic carbenes for disubstituted ketenes or cinchona alkaloids for monosubstituted ketenes, Ts=4‐toluenesulfonyl).